2008
DOI: 10.4049/jimmunol.180.3.1729
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Lyse T Regulatory Cells That Expand in Response to an Intracellular Pathogen

Abstract: We evaluated the capacity of NK cells to influence expansion of CD4+CD25+FoxP3+ regulatory T cells (Tregs) in response to microbial Ags, using Mycobacterium tuberculosis as a model. We previously found that Tregs expand when CD4+ cells and monocytes are exposed to M. tuberculosis. Addition of NK cells that were activated by monokines (IL-12, IL-15, and IL-18) or by exposure to M. tuberculosis-stimulated monocytes reduced Treg expansion in response to M. tuberculosis. NK cell inhibition of Treg expansion was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
106
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(116 citation statements)
references
References 54 publications
(60 reference statements)
7
106
0
1
Order By: Relevance
“…NK cells mediate their effects through cellular cytotoxicity alongside the production of a range of cytokines and other immunoregulatory mediators (14)(15)(16)(17)(18)(19). Early resistance to intracellular pathogens, including M. tuberculosis, can be driven by IFN-g production and lysis of infected cells and through modulatory effects on T regulatory responses (20)(21)(22). Several studies have suggested that crosstalk between NK cells and APCs, such as dendritic cells (DCs) and macrophages (MFs), during the early phases of the immune response influences the type of adaptive immunity that follows (23)(24)(25).…”
mentioning
confidence: 99%
“…NK cells mediate their effects through cellular cytotoxicity alongside the production of a range of cytokines and other immunoregulatory mediators (14)(15)(16)(17)(18)(19). Early resistance to intracellular pathogens, including M. tuberculosis, can be driven by IFN-g production and lysis of infected cells and through modulatory effects on T regulatory responses (20)(21)(22). Several studies have suggested that crosstalk between NK cells and APCs, such as dendritic cells (DCs) and macrophages (MFs), during the early phases of the immune response influences the type of adaptive immunity that follows (23)(24)(25).…”
mentioning
confidence: 99%
“…However, early in immune responses NK cells are further activated and recruited to tissue sites where they perform effector functions. It was recently reported that NK cells were capable of lysing pathogen-induced Treg cells, which expressed UL16-binding protein [40]. In contrast, it was demonstrated that Treg cells in a tumor microenvironment kill NK cells in a granzyme-B-dependent fashion [41].…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Sentman and colleagues 166 have shown the in vitro efficacy of T cells expressing CARs based on NKG2D. These T cells are cytotoxic against tumour cells, but also against immunosuppressive myeloid cells and T Reg cells that transiently express NKG2DLs [167][168][169] . These 'improved' NKG2D CARs present advantages over the endogenous NKG2D receptors, because some of these CAR variants that do not associate with DAP10 (the signalling adaptor required for endogenous NKG2D receptor expression) are not down-modulated after exposure to the ligands 170 .…”
Section: Using Nk Cells For Cancer Therapymentioning
confidence: 99%